2015
DOI: 10.1186/s40478-014-0181-z
|View full text |Cite
|
Sign up to set email alerts
|

Early detection of structural abnormalities and cytoplasmic accumulation of TDP-43 in tissue-engineered skins derived from ALS patients

Abstract: Amyotrophic lateral sclerosis (ALS) is an adult-onset disease characterized by the selective degeneration of motor neurons in the brain and spinal cord progressively leading to paralysis and death. Current diagnosis of ALS is based on clinical assessment of related symptoms. The clinical manifestations observed in ALS appear relatively late in the disease course after degeneration of a significant number of motor neurons. As a result, the identification and development of disease-modifying therapies is difficu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 41 publications
0
48
0
1
Order By: Relevance
“…However, neuronal aggregates negative for TDP‐43, but enriched in other proteins (such as p62), are considered pathognomonic for this group of patients . Furthermore, TDP‐43 dysfunctions may or may not characterize cell lineages with mutant C9ORF72 . Herein, of the mutant C9ORF72 patients recruited, cytoplasmic accumulation of TDP‐43 was manifest in monocytes in all and also in lymphocytes only in one.…”
Section: Discussionmentioning
confidence: 92%
“…However, neuronal aggregates negative for TDP‐43, but enriched in other proteins (such as p62), are considered pathognomonic for this group of patients . Furthermore, TDP‐43 dysfunctions may or may not characterize cell lineages with mutant C9ORF72 . Herein, of the mutant C9ORF72 patients recruited, cytoplasmic accumulation of TDP‐43 was manifest in monocytes in all and also in lymphocytes only in one.…”
Section: Discussionmentioning
confidence: 92%
“…Page 5 of 35 Nardo et al, 2011;Noto et al, 2011;Pare et al, 2015). Only 5-10% of familial and 1% of sporadic ALS cases carry TDP-43 mutations (Lattante et al, 2012;Millecamps et al, 2010), yet wild-type TDP-43 is incorrectly processed in the majority of patients with ALS (Janssens and Van Broeckhoven, 2013).…”
Section: Accepted Manuscriptmentioning
confidence: 98%
“…In addition, in TES reconstructed from asymptomatic C9ORF72 carriers of GGGGCC repeat expansion, cytoplasmic TDP‐43 inclusions were detected. Importantly, the same authors demonstrated with immunohistochemistry that TDP‐43 cytoplasmic inclusions are present in native skin biopsies (Paré et al., ). Also, TDP‐43 immunohistochemical signal intensity is higher in the skin of ALS patients compared with control patients (Suzuki et al., ).…”
Section: Introductionmentioning
confidence: 86%
“…The ALS‐TES contained both fibroblasts and keratinocytes. ALS‐TES reveals stratum corneum detachment, abnormal dermo–epidermal junction and collagen misorganization, as opposed to TES from normal individuals (Paré et al., ). In the ALS‐TES, TDP‐43 aggregates are observed, indicating that these aggregates can be detected outside the nervous system.…”
Section: Introductionmentioning
confidence: 99%